Freediving, Hypoxia, and Inflammation: Physiological Adaptations and Interactions between HIF and NF-κB - Amalina Fakhriah; Novi Silvia Hardiany; Iswanti, Febriana Catur (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Freediving presents a unique set of physiological challenges and adaptations, making it a subject of interest for researchers studying the effects of extreme environmental conditions on the human body. There is a complex interplay between freediving, hypoxia, immune responses, and inflammation, shedding light on the physiological effects of freediving on the human body. This article describes how HIF and NF-κB interact during hypoxia and inflammation, including their synergistic effects and signaling pathways. The regulatory loop involving these transcription factors is highlighted, providing insight into their linked roles in modulating the cellular response to hypoxia and inflammation.